Bio-Math Synergy: Creating Relevant Cross-Disciplinary Learning in the Digital Age - Fitri, Fitri; Hasbi, Muhammad (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
High school learning is generally divided into isolated subjects, with biology deemed rote learning and math as formulas with no practical value. In the data-driven digital age, high school students find it difficult to connect statistical or algebraic concepts to biological events like the spread of viruses and changes in ecosystems. Lack of connection between these fields reduces computational thinking and scientific literacy. This study examines whether the